Strategic Management Accounting Practices and Organizational Performance Through Maqasid Shariah Orientation - Anita Kusuma Dewi; Umiaty Hamzani; Maulidia Berlianti; Mardiah Kenamon (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study investigates the effect of Strategic Management Accounting Practices on Organizational Performance by examining the mediating role of Maqasid Shariah Orientation in Sharia-based institutions and organizations in Indonesia. Design/methodology/approach – A quantitative explanatory design was employed using data collected from 250 managerial employees through a five-point Likert-scale questionnaire. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding/Results – Strategic Management Accounting Practices positively influence Organizational Performance and Maqasid Shariah Orientation. Maqasid Shariah Orientation also exerts a positive effect on Organizational Performance and significantly mediates the relationship between Strategic Management Accounting Practices and Organizational Performance. Originality/Value – This study proposes an integrative model demonstrating that Maqasid Shariah Orientation strengthens the contribution of Strategic Management Accounting Practices to organizational performance, offering insights for organizations seeking sustainable and value-based governance.